2010
DOI: 10.1007/s11999-009-1162-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Osteoporosis Risk in Orthopaedic Patients

Abstract: Level I, diagnostic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 22 publications
4
22
2
2
Order By: Relevance
“…Clinical studies have demonstrated that smoking (Rozental et al. ) and estrogen deficiency (Popat et al. ) are important determinants for low bone density.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinical studies have demonstrated that smoking (Rozental et al. ) and estrogen deficiency (Popat et al. ) are important determinants for low bone density.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have demonstrated that smoking (Rozental et al 2010) and estrogen deficiency (Popat et al 2009) are important determinants for low bone density. On account of this close relationship, the impact of smoking on estrogen levels, bone remodeling markers, vitamin D-PTH axis, and other sex hormones has been extensively investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Имеется обширная доказательная база, что пере-ломы в области лучевой кости в типичном месте, дис-тальном отделе плечевой кости, позвоночнике и прок-симальном отделе бедренной кости ассоциируются с повышением риска последующего перелома, что явля-ется отражением снижения МПК после предшествую-щего перелома [23,61].…”
Section: обзоры литературы № 3/2013 остеопороз и остеопатииunclassified